2022
DOI: 10.1002/adfm.202113235
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks Derived Electrolytes Build Multiple Wetting Interfaces for Integrated Solid‐State Lithium–Oxygen Battery

Abstract: Solid-state lithium-oxygen (Li-O 2 ) batteries are considered as the next-generation solution for high-safety energy storage systems to overcome the persistent problems associated with liquid battery systems. However, the absence of stable solid-state electrolytes (SSEs) and the design complexity of functional solid-state cathode (SSC) remains a fundamental challenge. Here, a high-performance solid-state Li-O 2 battery is presented with Li-ion-conducted UiO-67 (UiO-67-Li) as SSEs and UiO-67-Li@reduced graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Besides, the EIS results revealed that H 2 O and KO 2 /DMSO treatments have a negligible effect on NH 2 -MIL-125-Li (Figure S26). 18 Advanced comprehensive performance of NH 2 -MIL-125-Li could also be confirmed compared with other different reported MOFs applied in Li-ion batteries (Figure S27 and Table S1). 5b).…”
Section: ■ Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Besides, the EIS results revealed that H 2 O and KO 2 /DMSO treatments have a negligible effect on NH 2 -MIL-125-Li (Figure S26). 18 Advanced comprehensive performance of NH 2 -MIL-125-Li could also be confirmed compared with other different reported MOFs applied in Li-ion batteries (Figure S27 and Table S1). 5b).…”
Section: ■ Introductionsupporting
confidence: 67%
“…Besides, the EIS results revealed that H 2 O and KO 2 /DMSO treatments have a negligible effect on NH 2 -MIL-125-Li (Figure S26). Advanced comprehensive performance of NH 2 -MIL-125-Li could also be confirmed compared with other different reported MOFs applied in Li-ion batteries (Figure S27 and Table S1). The superior ionic conductivity behavior, electrochemical stability, and chemical stability would guarantee their great potential as SSEs in solid-state Li–O 2 batteries.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…368,369 MOF-based aerogels recently attracted much attention as promising electrode materials for EES due to their high surface areas and interconnected networks of multimodalities, which provide short diffusion paths and fine dispersion of active sites to maximize the rate of reactions. 370–373 Although the direct use of many MOFs in electrochemical devices is limited due to their poor electrical conductivity and low chemical stability, metal–carbon complex nanostructures have shown potential to deliver desired electrochemical properties. 374–376 This section highlights how such tuneable MOGs derived materials advance the performance of lithium-ion batteries (LIBs) and supercapacitors.…”
Section: Applicationsmentioning
confidence: 99%
“…[8][9][10][11] Recently, several state-of-the-art strategies have been proposed to circumvent the above issues, mainly including constructing an artificial SEI film to stabilize the electrode surface and reduce side reactions between the electrolyte and electrode, 12,13 optimizing electrolyte composition to enhance the stability of the SEI film, [14][15][16][17] and developing solid-state electrolytes with high modulus to protect the separator from dendrites. [18][19][20][21] Although these strategies can effectively suppress the growth of Li dendrites and improve the electrochemical performance to some extent, the SEI-modified LMAs with the "hostless" feature hardly withstand the large volume change during long-term cycling and hinder further development of LMBs. [22][23][24] By contrast, accommodating the deposited Li metal into the three-dimensional (3D) current collectors has the potential to become a more effective strategy to resolve these intractable problems.…”
Section: Introductionmentioning
confidence: 99%